Kesenjangan antara Harapan dan Pelayanan Pasien JKN terhadap Aspek Hubungan Antar Manusia di Instalasi Rawat Inap RSUD Haji Makassar - Idarwati Mustafa; Andi Mikhrunnisai; Anugerah Yanuar Azis; Khusnul Khatimah (Lentera Pena Cendekia, 2025)
Interpersonal relationships in healthcare services, particularly in inpatient settings, are fundamental aspects that significantly influence patients’ perceptions and satisfaction levels. Among participants of the National Health Insurance (JKN) program, discrepancies are often observed between their expectations and the actual services received. These gaps commonly relate to communication, empathy, and the attentiveness of healthcare providers toward patients. This study aims to identify the differences between patient expectations and the services received, specifically regarding interpersonal aspects in the inpatient care unit of RSUD Haji Makassar. This research employed a quantitative design with a cross-sectional approach. A total of 98 respondents patients from class I, II, and III inpatient services were selected using quota sampling from a population of 41,663 patients. Data were collected through a structured questionnaire and analyzed using univariate methods and the Importance Performance Analysis (IPA) approach. The results showed that the average expectation score was 3.16, while the average score of received services was 3.06. The overall conformity level was 96.89%, indicating a noticeable gap that needs improvement. The highest satisfaction was found in the item